2004
DOI: 10.1038/modpathol.3800075
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic peripheral blood findings in human ehrlichiosis

Abstract: Human ehrlichiosis is a potentially fatal tick-borne illness if not treated promptly. Ehrlichia infection is difficult to diagnose as the organism does not grow in standard blood culture medium and serological confirmation of infection takes several days to weeks. The most timely way of confirming Ehrlichia infection is identification of characteristic cytoplasmic morulae in peripheral blood leukocytes. A total of 23 patients with clinical and laboratory findings suggesting a rickettsial infection were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 23 publications
(20 reference statements)
0
24
0
4
Order By: Relevance
“…In a similar evaluation of hematological response of chickens with, and without, infection by Aegyptianella pullorum, Nazifi et al (2008) found no evidence of an innate immune (i.e., white blood cell) response; however, less than 1% of red blood cells were infected in that study. Humans infected with the bacteria, Ehrlichia chaffeensis, which infects white rather than red blood cells, have fewer white cells than uninfected individuals (Hamilton et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar evaluation of hematological response of chickens with, and without, infection by Aegyptianella pullorum, Nazifi et al (2008) found no evidence of an innate immune (i.e., white blood cell) response; however, less than 1% of red blood cells were infected in that study. Humans infected with the bacteria, Ehrlichia chaffeensis, which infects white rather than red blood cells, have fewer white cells than uninfected individuals (Hamilton et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, pancytopenia due to ehrlichiosis has prompted bone marrow aspirate and biopsy, which typically reveals normocellular or hypercellular marrow (128,156). In some patients, morulae might be observed in monocytes in peripheral blood (157) (Figure 28) and occasionally in CSF (158,159) or bone marrow. In this context, a routine blood smear can provide a presumptive clue for early diagnosis; however, the visualization of morulae still requires confirmatory diagnostic testing (see Confirmatory Diagnostic Tests).…”
Section: Laboratory Findingsmentioning
confidence: 99%
“…Patients with ehrlichiosis may present with fever, headache, myalgia, rash, nausea, vomiting, and laboratory findings of thrombocytopenia, leukopenia, anemia, and elevated liver enzyme numbers (4, 6, 9, 10). In peripheral blood, E. chaffeensis generally has tropism for monocytes and E. ewingii tropism for granulocytes (1,4,6). Anaplasmosis has similar symptoms and was formerly referred to as human granulocytic ehrlichiosis (11,12).…”
mentioning
confidence: 99%
“…On peripheral smears made using a Wright-Giemsa stain, E. chaffeensis, E. ewingii (Fig. 1), and A. phagocytophilum appear as basophilic clusters of intacytoplasmic bacteria referred to as morulae (1,11,15). E. murislike bacteria have yet to be morphologically described in vivo but infect granulocytic and monocytic cell lineages in cell culture (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation